The m6A Reader IGF2BP2 Promotes Oral Squamous Cell Carcinoma Progression by Maintaining UCA1 Stability - Zhang, Duheyi; Mai, Lianxi; Zhang, Lizao; Huang, Guoxin; Lin, Zhaoyu; Wang, Shuang; Rao, Guangxin; Xie, Shule; Pan, Chaobin (Recent Patents on Anti-Cancer Drug Discovery, 2025)
IntroductionN6-methyladenosine (m6A) modifications of RNAs are associated with many cancer types. Nevertheless, the function of the m6A reader IGF2BP2 in oral squamous cell carcinoma (OSCC) has yet to be ascertained.AimsThe objective of this investigation was to elucidate the role of IGF2BP2 in OSCC and delineate the associated mechanisms.MethodsElevated expression of IGF2BP2 was observed in OSCC, and this overexpression significantly correlated with adverse prognostic outcomes in patients with OSCC. In vitro analyses demonstrated that silencing of IGF2BP2 attenuated the proliferation, migration, and invasion capabilities of oral cancer cells while concurrently promoting apoptosis.ResultsIn vivo experiments demonstrated that IGF2BP2 promoted OSCC growth. RNA-seq and m6A-seq were utilized to elucidate the downstream targets of IGF2BP2. Through bioinformatic analysis, we identified the long noncoding RNA (lncRNA) UCA1 as a target. IGF2BP2 was found to maintain the stability of UCA1 in an m6A-dependent manner by binding to m6A-modified UCA1 and plays an oncogenic role in OSCC through UCA1.ConclusionIn conclusion, we identified IGF2BP2 as a prognostic biomarker of OSCC, and the IGF2BP2-UCA1 axis was found to promote OSCC progression and may perform as a novel therapeutic target.
Keywords: RNA